1973
DOI: 10.1002/bip.1973.360120810
|View full text |Cite
|
Sign up to set email alerts
|

Heats of thermally induced helix–coil transitions of DNA in aqueous solution

Abstract: synopsisThermal denaturation of calf thymus DNA at both alkaline and neutral pH values was studied by differential scanning calorimetry. It was shown that the dependence of the enthalpy of transition on pH and salt concentration could be accounted for on the basis of a heat capacity change of +40 cal deg-1 (base pair)-'. In the pH range between 10.3 and 11.3, a release of 0.6 proton per base pair was calculated from the pH dependence of the melting temperature. The heat effect associated with the release of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

1974
1974
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 26 publications
3
13
0
Order By: Relevance
“…In accordance with the common point of view in alkaline medium only coil DNA form can be deprotonated (18)(19)(20). There is only one paper (21) known to us where it was shown that deprotonation occurs in helical DNA characterized by high GC content (GC=72%).…”
Section: Experimental Data and Results Of Calculation For Alkaline Mesupporting
confidence: 52%
See 1 more Smart Citation
“…In accordance with the common point of view in alkaline medium only coil DNA form can be deprotonated (18)(19)(20). There is only one paper (21) known to us where it was shown that deprotonation occurs in helical DNA characterized by high GC content (GC=72%).…”
Section: Experimental Data and Results Of Calculation For Alkaline Mesupporting
confidence: 52%
“…Let us consider the model of DNA deprotonation supposed in (18)(19)(20). I) helical DNA form cannot release protons (pK 2 ; =+co); 2) DNA deprotonation is a noncooperative process (w 1 =0); 3) guanine and thymine may be deprotonated in coil DNA form.…”
Section: Experimental Data and Results Of Calculation For Alkaline Mementioning
confidence: 99%
“…Note that the size of the co-operatively melting unit cancels out of equation (6.9) for d2^/dlna± (Record, 1975). Calorimetric studies on nucleic acid conformational transitions indicate that the quantity RT^/AH^ is a con-stant (here designated fi) independent of temperature, counterion concentration, base composition and chain length, although dependent upon the strandedness of the forms involved and possibly upon the nature of the counterion and the pH (Krakauer & Sturtevant, 1968;Privalov, Ptitsyn & Birshtein, 1969;Klump & Ackermann, 1971;Shiao & Sturtevant, 1973;Breslauer, Sturtevant & Tinoco, 1975; see Record, Woodbury & Lohman, 1976 b). An experimental value for A5 M+ can be obtained for T4 DNA from the calorimetric data of Privalov et al (1969) (/?= 50 + 2 deg, independent of NaCl concentration and absolute temperature) and the melting data of Record (1975), which give d2^/dlna± = 8-9 ±0-2 over the range 2-5 x io~3 M ^ [NaCl] s$ o-1 M. Over this range (8 In y±/8 In a±) is variable but small, an average value for NaCl (Robinson & Stokes, 1959) being 0-05 ± 0-03, so a ~ 0-95.…”
Section: Transitionsmentioning
confidence: 99%
“…We are not aware of such data for DNA containing MgCl 2 , but some results in the presence of only monovalent counterions do exist in the literature. Experimental values of ⌬G m,0 (C Na ) at the standard temperature T o can be determined from the dependence of melting enthalpy (⌬H m ) on melting temperature from the following relation (Shiao and Sturtevant, 1973):…”
Section: Dependence Of ⌬G M On Nacl Concentrationmentioning
confidence: 99%